Cystic partially differentiated nephroblastoma in infant: A case report - Sah, Anil Kumar; Nepal, Umesh; Pandey, Greta (Journal of Kathmandu Medical College, 2021)
Cystic partially differentiated nephroblastoma is a variant of the multilocular cystic renal tumour, considered as the bridge between cystic nephroma and cystic Wilm's tumour. It usually occurs in children below the age of two years with predominance in male. Histopathology is considered a diagnostic modality. Neoadjuvant chemotherapy and adjuvant radiotherapy may benefit the patient in selected cases. Here, a five-month-old boy who presented with painless gradually increasing right sided abdominal mass is reported. Imaging and fine needle aspiration cytology findings were inconclusive to reach the diagnosis. The histopathology after a radical nephrectomy concluded the diagnosis of cystic partially differentiated nephroblastoma.